Spectrophotometer is useful for assessing vitiligo and chemical leukoderma severity by quantifying color difference with surrounding normally pigmented skin. Issue 2 (22nd October 2017) - Hayashi, M.; Okamura, K.; Araki, Y.; Suzuki, M.; Tanaka, T.; Abe, Y.; Nakano, S.; Yoshizawa, J.; Hozumi, Y.; Inoie, M.; Suzuki, T.
Abstract: Background: Acquired skin hypopigmentation has many etiologies, including autoimmune melanocyte destruction, skin aging, inflammation, and chemical exposure. Distinguishing lesions from normally pigmented skin is clinically important to precisely assess disease severity. However, no gold standard assessment method has been reported. We aimed to investigate whether spectrophotometers are useful for assessing vitiligo and rhododendrol (4‐(4‐hydroxyphenol)‐2‐butanol) (Rhododenol ® )‐induced leukoderma disease severity by quantifying skin color. Methods: Mexameter ® MX18 and CM‐700d spectrophotometer were used for assessing vitiligo/leukoderma by measuring melanin index, L * a * b * color space, and Δ E * ab value, which represents the color difference between two subjects and is calculated by the values of L * a * b *. Results: MX18 and CM‐700d can quantitatively distinguish vitiligo/leukoderma from normally pigmented skin based on melanin index. CM‐700d consistently quantified the color of vitiligo/leukoderma lesions and surrounding normally pigmented skin in L * a * b * color spaces and Δ E * ab . Δ E * ab is well correlated with melanin index and clinical appearance. Conclusion: Δ E * ab has been frequently used in aesthetic dentistry; however, current study is the first to use it in the measurement of skin color. Δ E * ab seems to be a useful parameter to evaluate the color contrast between vitiligo/leukoderma and surrounding normally pigmented skin and can be used to evaluate disease severity and patient's quality of life.